Multidimensional characterization of separation processes – Part 2: Comparability of separation efficiency. (1st May 2020) - Buchmann, Markus; Schach, Edgar; Leißner, Thomas; Kern, Marius; Mütze, Thomas; Rudolph, Martin; Peuker, Urs A.; Tolosana-Delgado, Raimon
Highlights: Flexibility of the concept to apply to various separation processes. Comparability of separation efficiency by entropy of different separation processes. Weighted Entropy to improve comparability by referring to any feed material. Identification of problematic mineral behaviour through weighting with specific mineral mass distribution. Estimation of suitable process parameters for individual feed materials. Abstract: Following the proposal of deriving statistical entropy maps from multidimensional separation curves, an extension is proposed to allow to compare the separation efficiency of various separation processes. This is achieved by integrating the entropy map weighted by the mass distribution of the particles in the feed. This proposal has several advantages: its straightforward extension to multidimensional partition curves, its scalar value (which allows for a natural ranking of processes), its flexibility to adapt to each and every feed, and its non-parametric character. A typical dynamic air classification process of an iron ore is presented as an example.